Analisis Multi Varian Pemesinan Bor Magnesium AZ31B Menggunakan Metode Taguchi Gray Relational Analysis - Leksono, Panji Mario; Yanuar Burhanuddin; Gusri Akhyar Ibrahim; Suryadiwansa Harun (Politeknik Caltex Riau, 2024)
This research aims to obtain optimal drilling machining parameters in response to tool life, surface roughness and response to the influence of electric current. Tool life is a derivative of the wear value obtained. The Taguchi method is often used to determine optimal quality in single response manufacturing processes. However, when there is more than one response, researchers often use the Gray Relational Analysis (GRA) method. This research was carried out on the response of tool life, surface roughness and the effect of electric current on Magneisum AZ31B type material using four factors and mix levels. The chisel diameters used are 8 mm and 10 mm. The spindle speed is set at 890 rpm, 1270 rpm, 1700 rpm and 2000 rpm, feeding uses values of 0.1 mm and 0.3 mm, while the point angles used are 118° and 135°. The optimal results obtained in this research were using a tool diameter of 8 mm, spindle speed of 890 rpm, feeding of 0.1 mm, and point angle of 118°. Keywords: Drilling, Taguchi Method, Gray Relational Analysis, Tool Wear, Surface Roughness, Electric Current.